2018
DOI: 10.1186/s13148-018-0486-z
|View full text |Cite
|
Sign up to set email alerts
|

H19 overexpression promotes leukemogenesis and predicts unfavorable prognosis in acute myeloid leukemia

Abstract: BackgroundThe long non-coding RNA H19 plays a crucial role in solid tumor initiation and progression. However, the potential role of H19 and its clinical significance in acute myeloid leukemia (AML) remain largely elusive.MethodsH19 expression was detected by qPCR, and clinical significance in AML patients was further analyzed. The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) data for AML were used as validation cohorts. The roles of H19 in cell proliferation and apoptosis were determined by ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 40 publications
1
88
0
Order By: Relevance
“…11,21 Therefore, it is important to illuminate the resistance mechanism and to overcome H19 is a long chain non-coding RNA with length of 2.3 kb. 20 Among AML, H19 overexpression correlated with poor chemotherapy response and shorter overall survival 36 Taken together, we deduced that H19 may play a role in drug resistance during leukemogenesis. [31][32][33][34] Our previous study revealed that H19 expression level, associated with its promoter methylation status, was significantly upregulated in CML patients involving in disease progression.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…11,21 Therefore, it is important to illuminate the resistance mechanism and to overcome H19 is a long chain non-coding RNA with length of 2.3 kb. 20 Among AML, H19 overexpression correlated with poor chemotherapy response and shorter overall survival 36 Taken together, we deduced that H19 may play a role in drug resistance during leukemogenesis. [31][32][33][34] Our previous study revealed that H19 expression level, associated with its promoter methylation status, was significantly upregulated in CML patients involving in disease progression.…”
Section: Discussionmentioning
confidence: 68%
“…Real-time quantitative PCR (RQ-PCR) was conducted to evaluate the mRNA and miRNA expression levels in the DAC resistant cells as previously described using the primer sets (Table S1). [15][16][17][18][19]…”
Section: Rq-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that EZH2 dysregulation was significantly associated with HOX gene family, THBS1, CDKN2B, PAX2 and H19, which was reported highly correlated with haematopoiesis and leukaemogenesis. [23][24][25][26][27] Moreover, for microRNAs, we observed that EZH2 expression was negatively correlated with several mi-croRNAs such as miR-21, miR-23a, miR-500, let-7a-3, miR-362, let-7e…”
Section: Discussionmentioning
confidence: 87%
“…The effect of HSCT on survival of AML patients among EZH2 low-and high-expressed groups. We found that EZH2 dysregulation was significantly associated with HOX gene family, THBS1, CDKN2B, PAX2 and H19, which was reported highly correlated with haematopoiesis and leukaemogenesis [23][24][25][26][27]. Survival was analysed though Kaplan-Meier analysis using Log-rank test between transplantation and chemotherapy in AML.…”
mentioning
confidence: 99%